CEO pay-risk sensitivity, firm policies, and 2009 Australian tax reforms. Issue 1 (5th December 2017) - Bian, Chao; Gan, Christopher; Li, Zhaohua; Hu, Baiding
Abstract : Purpose: The purpose of this paper is to examine the effects of chief executive officer (CEO) vega on firm policies in the Australian share market based on a panel data set drawn from the 137 Australian public firms for the period 2003-2012. Design/methodology/approach: To allow mutual causation between our variables, the authors use the two-stage least squares estimation method, controlling for firm fixed effects. The authors use the difference-in-differences model to test whether the 2009 Australian tax reforms may discourage high-vega CEOs to take value-enhancing risks. Findings: The authors find the evidence that vega induces CEOs to adopt the riskier financial policy in the Australian capital market. This evidence is further supported by the negative association between vega and firm conservative activities including cash and hedging policies. Further, the result shows that the 2009 tax reforms reduce the CEOs' willingness to engage in risky financial policy. This finding implies that regulators may restore the 2009 reforms' "deferred tax point" back to its pre-2009 form. Originality/value: Based on the study's results, firms should grant CEOs more out-of-the money options with a longer time to expiration to offset the 2009 tax reforms' negative impact on the CEO's incentive to take value-enhancing risks.